Implementation of school inspection in TS25 schools in Negeri Sembilan, Malaysia - Md Ali, Nurul Jawahir (2021)
School inspection is an important instrument in educational administration to maintain the quality of education. Despite its positive intend, numbers of undesirable effects of school inspection have been reported. The occurrence of negative effects has raised concern as it can undo the intended effects of inspection. There’s an increasing trend in studying the effects of school inspection. However, little is known about how school inspection is experienced by the inspectees and how its impact on school improvement can be accomplished. With numerous studies on school inspection in Europe and inadequate understanding on its experience that can describe the underlying reasons for the unintended effects, a study that focuses on this matter beyond the European context needs to be conducted. Therefore, two research questions were developed to seek and explore on how school inspection is experienced and perceived by teachers and school administrators and how does school inspection facilitate schools to improve their practices in teaching and school management. Frameworks of School Inspection Effect (Ehren & Visscher, 2006; de Wolf & Janssens, 2007) and Model of Effects and Effectiveness of School Inspection (Landwehr, 2011) were applied in developing the theoretical framework. By using qualitative case study approach, two schools in Negeri Sembilan that were inspected under ‘Inspection on Implementation of Transformation School Program 2025’ were studied. Data was collected through 9 semi structured interviews followed with document analysis and were thematically analysed. The findings have captured detailed account about the process before and during inspection along with the favourable and unfavourable response to school inspection, and the positive perception on school inspectors. Despite initial emotional disturbances and perceived burden, participants accepted the given feedback and have positive perception on the purpose of school inspection as a process to monitor and ensure schools’ quality and standard enforcement, which helps toward school improvement. This study has revealed that school inspectors’ positive attitude along with the school personnel role in accepting the feedback has contribute to positive outcomes, in which schools are able to make improvement in both areas of teaching and school management. It is concluded that the pre-inspection process like the time selection and duration of preparation as well as the inspectors’ attitude are important in ensuring the effectiveness of school inspection. However, school personnel also play key role in accepting the given feedback and turning it into meaningful action for the sake of school improvement. Although the inspection was deemed as burdensome, it is still regarded as beneficial by the participants and school improvement is successfully achieved. It is recommended for school inspector to possess positive traits as mentioned in the findings to promote positive and beneficial process of school inspection. With the given highlight on the positive process of school inspection that can help school towards improvement, School Inspectorate would be able to reflect its approach and practice in conducting school inspection. Finally, school administrator has important role too in promoting positive acceptance of school inspection finding among school members. This study also offers a conceptual framework that contribute toward the body of knowledge in the field of educational administration and outlining suggestions for improving the practice of administering school via inspection.